2014
DOI: 10.1080/02723638.2014.961359
|View full text |Cite
|
Sign up to set email alerts
|

“They want to live in the Tremé, but they want it for their ways of living”: gentrification and neighborhood practice in Tremé, New Orleans

Abstract: In this study, I deploy an ethnographic approach to analyze the detrimental effects of gentrification on longstanding residents in New Orleans' Tremé neighborhood. I focus on conflicts between long-established residents and gentrifiers over the use of neighborhood space on a day-to-day basis as a means for examining the consequent changes in neighborhood life. As their neighborhood gentrifies, long-term residents of Tremé must contend with greater policing, the erosion of place-based knowledge, practices, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…The disaster has disproportionately affected the city’s black communities through a series of detrimental social and economic forces amplified by local policy decisions about housing, land use, and environmental protection (Ehrenfeucht and Nelson 2012; Parekh 2015; Lovet 2013; Deitz and Barber 2015; Johnson 2015). These differences were manifested in differential out-migration, destruction of homes, and an ability to return and rebuild.…”
Section: Discussionmentioning
confidence: 99%
“…The disaster has disproportionately affected the city’s black communities through a series of detrimental social and economic forces amplified by local policy decisions about housing, land use, and environmental protection (Ehrenfeucht and Nelson 2012; Parekh 2015; Lovet 2013; Deitz and Barber 2015; Johnson 2015). These differences were manifested in differential out-migration, destruction of homes, and an ability to return and rebuild.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found long‐term residents describe a policing‐gentrification link in places as disparate as New York City, Chicago, Los Angeles, San Francisco, Seattle, New Orleans, Vancouver, and Washington DC (Fagan and MacDonald ; Freeman ; Herbert ; Lyons et al. ; Maharawal ; Parekh ; Rai 2011; Saunders and Kirby Smith ). Two studies have speculated it is new neighbors’ demands for police that spur more policing (Freeman ; Parekh ).…”
Section: Crime Complaints and New Residentsmentioning
confidence: 99%
“…; Maharawal ; Parekh ; Rai 2011; Saunders and Kirby Smith ). Two studies have speculated it is new neighbors’ demands for police that spur more policing (Freeman ; Parekh ). One long‐term resident of gentrifying Harlem put it this way to sociologist Lance Freeman: “[I]f you sit on the benches the police will come along and point to the no loitering sign and say you can't stay here.…”
Section: Crime Complaints and New Residentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gentrification is evolving, through powerful recombinants of cognitive‐capitalist production and wealth accumulation (Scott ), bio‐political management of precarious life amidst intensifying inequalities (Murray ), all‐out ‘domicide’ of the material spaces of daily life (Zhang ), local symbolic struggles over embedded cultural meanings of festivals celebrating the memories of the dead (Parekh ), and an almost unimaginable diversity of other localised expressions of divisive competition (CBC News ; Young ). But just as evolutionary theory was kidnapped in previous generations, we can take it back.…”
Section: Reclaiming (R)evolutionary Urbanismmentioning
confidence: 99%